Structural variants and susceptibility to common human disorders - Estivill, Xavier (Henry Stewart Talks, 2009)
Complex genetic diseases, Genome-wide association studies, Human genome variation, Type of structural variants, Detection of CNVs, CNV algorithms, Next generation sequencing, Pain end mapping, Effects of rare CNVs on complex disorders, Common CNV in common disorders, LCE3C and LCE3E, Copy number variants in psoriasis, Structural variation in human disease
Archived at 2021/02/25